PEMBERIAN PASAK BUMI MEMENGARUHI KADAR TESTOSTERON DAN SPERMATOZOA KAMBING PERANAKAN ETAWA (The Administration of Eurycoma longifolia Jack Affect the Level of Testosterone and Spermatozoa of Etawa Crossbreed Goat) - Pratomo, Hurip; Yudi, Yudi (Universitas Syiah Kuala, 2016)
ABSTRACT The study aimed to find out the effect of Eurycoma longifolia Jack on testosterone level and spermatozoa quality of Etawa crossbreed goat. Goats were divided into two treatment groups, three goats each. Group 1 (K1) was control group which given orally 20 ml of distilled water every morning at 9:00 am for six days, and group 2 (K2) was administered with Eurycoma longifolia with the dose of 90 mg/kg bw in 20 ml of distilled water orally every morning at 9:00 am for six days. The concentration of testosterone was measured on day 1, 3, and 6 using the method of enzyme-linked immunosorbent assay (ELISA). The quality of sperm consisted of concentration and percentage of life sperm. The results showed that level of testosterone on K2 increased started from day 1 (9.36 ng/ml) to day 6 (12.43 ng/ml) (P0.05). The percentage of life spermatozoa increased higher on K2 compare to K1 on day 3 to day 6, that was 88.6 and 89.8% on K1 to 91.0 and 92.7% on K2. In conclusion, the administration of pasak bumi with the dose of 90 mg/kg bw in 20 ml of distilled water for 6 days able to increase testosterone levels and percentage of life sperm of Etawa crossbreed goat.